1998
DOI: 10.1007/bf03347289
|View full text |Cite
|
Sign up to set email alerts
|

Angiosarcoma of the thyroid and concurrent hyperthyroidism

Abstract: We describe the exceptional association of an angiosarcoma of the thyroid and hyperthyroidism in a 74-year-old woman who presented with a toxic multinodular goiter of recent growth. This association reported in two other cases may not be fortuitous but due a vascular effect of the angiosarcoma contributing to the development of thyrotoxicosis. This case also illustrates the diagnostic difficulties and the poor prognosis of this tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…The histogenesis of these very aggressive tumors has been the matter of long standing controversies, because many authors believe that ASs are a variant of sarcomatoid carcinoma, in view of their nearly constant cytokeratin positivity in the neoplastic elements [17,19,25,26]. Other authors believe that true AS of the thyroid does exist, though it is rarely observed [2,4,8,9,14,18,21,31,33,37,39,40,41]. AS is apparently unrelated to the follicular cell lineage and develops mostly in endemic goiter areas, possibly being the result of malignant transformation of goitrous nodules that underwent recurrent intranodular hemorrhagic events with subsequent thrombotic and hyperplastic endothelial proliferations [11].…”
Section: Introductionmentioning
confidence: 95%
“…The histogenesis of these very aggressive tumors has been the matter of long standing controversies, because many authors believe that ASs are a variant of sarcomatoid carcinoma, in view of their nearly constant cytokeratin positivity in the neoplastic elements [17,19,25,26]. Other authors believe that true AS of the thyroid does exist, though it is rarely observed [2,4,8,9,14,18,21,31,33,37,39,40,41]. AS is apparently unrelated to the follicular cell lineage and develops mostly in endemic goiter areas, possibly being the result of malignant transformation of goitrous nodules that underwent recurrent intranodular hemorrhagic events with subsequent thrombotic and hyperplastic endothelial proliferations [11].…”
Section: Introductionmentioning
confidence: 95%
“…Angiosarcoma of the thyroid in association with hyperthyroidism is a rare condition and is reported in the literature [5]. The present case had also concurrent hyperthyroidism.…”
Section: Discussionmentioning
confidence: 49%
“…Most European authors think that these lesions represent true vascular neoplasms. 6,8,9,14,15,17,20,22,23,25 Authors who accept the vascular nature of these specimens base their assertion on the factor VIII immunoreactivity of the neoplastic cells. 21,28,29 The vascular nature has been corroborated by several ultrastructural studies that have supported an endothelial origin.…”
Section: Discussionmentioning
confidence: 99%